Pengelolaan Sampah Anorganik Rumah Tangga sebagai Media Tanam pada Masyarakat Desa Bumirejo dalam Program KPM MBKM-Br UNSIQ - Mustakhiqul Khilmi; Kholifatul Azizah; Hermawan Hermawan (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
The problem of waste at this time is constantly being discussed, all community activities always generate waste, so this is not only the responsibility of the government but also the whole community to process waste so that it does not have a negative impact on the surrounding environment. Waste management in Bumirejo Village is still limited to separating organic and inorganic waste. Organic waste in the form of food scraps will be used as animal feed, or used as fertilizer for plants, while inorganic waste is still collected collectively to be disposed of in landfills without being reused. This triggers the accumulation of inorganic waste which results in an increase in landfills in the local area, so that special handling is needed for this inorganic waste. The community service activities carried out in Bumirejo Village aim to increase public awareness regarding household waste reduction. In addition, one of the other goals is the utilization of household waste into something more useful in this case, namely as a planting medium. The approach method used in this service includes 2 methods, namely socialization and demonstration. The implementation of community service activities related to the management of inorganic household waste into planting media has been carried out well and smoothly. The understanding of the people of Bumirejo Village regarding the management of inorganic waste as a planting medium has increased.